Studies on the efficacy of Sarafin (Sarafloxacin hydrochloride) on vibrios associated with vibriosis in black tiger shrimp (Penaeus monodon) - Pakingking, Rolando Jr. V. (University of the Philippines in the Visayas, 1998)
In-viro activity of Sarafin (sarafloxacin hydrochloride) was determined against seven (7) luminous Vibrio harveyi isolated and three(3) non-luminous Vibrio spp. (V.parahaemolyticus, Vibrio sp, and V. alginolyticus) isolated from disease shrimp (Penaeus monodon) and rearing water, a strain of V. Anguillarum from diseased marine fish three (3) strains of vibrio (V. alginolyticus, V. vulnificus, and V. minicus) from diseased (Epinephelus coioides), and isolate of V. alginolyticus from diseased seabass (Lates calcalifer)., Bacterial susceptability was expressed as minimum inhibitory concentration (MIC) and minimum bacterial concentration (MBC). MIC and MBC values contained for all V. harveyi isolates ranged from <0.3 to 1.25 ug/ml. for the non-luminous Vibrio spp, MIC and MBC values ranged from <0.08 to 1.25 ug/ml. In-vivo tolerance of the larval and postlarval stages of P. monodon was also evaluated. the 24-hour static bioassay gave a tolerance level for the following: nauplii, mysis and postlarvae,<-10ug/m Sarafin, and protozoea, <- ug/ml Sarafin. Morphological deformities in the carapace, rostrum, and setae were noted among larvae exposed to >-50 ug/ml Sarafin. In-vitro and in-vivo results showed the potential use of Sarafin in larval rearing facilities to control the proliferation of luminous vibrios during disease epizootics. However, holistic assessment of its potential use in hatcheries using the current practice (i.e., immersion or bath method) appears limited due to some factors including the difficulty encountered in the dissolution of the drug in water, morphological deformities it caused to the test animals, and possible emergence of drug resistance due to inappropriate use.